Improved patient‐reported outcomes with iGlarLixi versus premix BIAsp 30 in people with type 2 diabetes in the SoliMix trial. Issue 12 (23rd August 2022) - Polonsky, William H.; Giorgino, Francesco; Rosenstock, Julio; Whitmire, Katherine; Lew, Elisheva; Coudert, Mathieu; Alvarez, Agustina; Nicholls, Charlie; McCrimmon, Rory J.
Abstract: Aim: To assess patient‐reported outcomes (PROs) in the SoliMix trial, which compared the efficacy and safety of iGlarLixi versus BIAsp 30 in people with type 2 diabetes (T2D). Materials and Methods: SoliMix (EudraCT: 2017‐003370‐13), a 26‐week, open‐label study, randomized (1:1) 887 adults with T2D and HbA1c ≥7.5%‐≤10.0% (≥58‐≤86 mmol/mol) on basal insulin plus oral antihyperglycaemic drugs (OADs) to once‐daily iGlarLixi or twice‐daily premix insulin, BIAsp 30. PROs were assessed using the Treatment‐Related Impact Measure Diabetes (TRIM‐D) and Global Treatment Effectiveness Evaluation (GTEE) questionnaires. Results: Over 26 weeks, iGlarLixi showed greater improvement from baseline versus BIAsp 30 in total TRIM‐D score (least squares mean difference [95% confidence interval]: 5.08 [3.69, 6.47]; effect size: 0.32) and in each TRIM‐D domain, with the greatest differences seen in diabetes management (8.47 [6.11, 10.84]) and treatment burden (6.95 [4.83, 9.07]). GTEE scores showed a greater proportion of participants and physicians rated a complete or marked improvement of diabetes control with iGlarLixi (80.5%, 82.8%) versus BIAsp 30 (63.3%, 65.1%) at week 26. Post hoc analyses showed that after adjusting for HbA1c, body weight and hypoglycaemia outcomes, iGlarLixi continued to show greater improvements in TRIM‐D total scores versus BIAsp 30. Conclusions: In addition to better glycaemic control, weight benefit and less hypoglycaemia, once‐daily iGlarLixi provided improved diabetes management, treatment burden and perceived effectiveness versus twice‐daily premix BIAsp 30, further supporting iGlarLixi as an advanced treatment option in people with suboptimally controlled T2D on basal insulin plus OADs.